Efficient Au0/C catalyst synthesized by a new method for acetylene hydrochlorination1. Issue 57 (25th June 2015) - Tian, Xiaohui; Hong, Guotai; Jiang, BinBo; Lu, Feipeng; Liao, Zuwei; Wang, Jingdai; Yang, Yongrong
<x xml:space="preserve">Abstract</x> A Au0/C catalyst for acetylene hydrochlorination was prepared via a novel method and an excellent Au dispersion and catalytic activity was obtained.